Meningkatkan Pemahaman Siswa SMK Negeri 4 Kota Serang Terhadap Peran Sistem Informasi Akuntansi di Sekolah - Aprilia, Sinta; Al Fayyadh, Bintang Mutiara; Septi, Berlian Aura; Desyanti, Rohilah; Kulsum, Umi (Jurnal Pemberdayaan Nusantara, 2025)
Accounting Information System (AIS) plays an important role in dealing with technological advances, especially in the education sector. At SMK Negeri 4 Serang City, there are still many students who do not understand the concept of AIS. Therefore, this community service program aims to improve students' understanding of AIS, so that they are able to prepare financial reports appropriately and accurately. This activity uses a simple method, namely the presentation of material directly to students through discussions and question and answer sessions. With this approach, it is expected that students can understand the concept of AIS and apply it in academic activities and daily life. In addition, students are also expected to be better prepared to face challenges in the world of work, especially in the field of accounting and finance. This program also provides an opportunity for schools to establish cooperation with industries or companies, in order to provide students with broader experience and knowledge about AIS.